Brown Tumor, a Deceptive and Rare Entity: A Case Report - Vaidya, Monasha; Rai, Ujwal; Gautam, Prerana; Yadav, Rekha; Sah, Bajrang Pd. (Medical Journal of Eastern Nepal, 2023)
A case of 27 years old male from Jhapa district, who presented to Oral and Maxillofacial department of B&C hospital with firm, non-tender swelling over buccal vestibule for 2 months. Computed tomography (CT) revealed an expansile lytic bony lesion with soft tissue component at the right hemimandible with cortical destruction. Provisional diagnosis of ameloblastoma was made. Incisional biopsy done and specimen was sent to the Pathology department. Haematoxylin and Eosin- stained slides revealed disorderly, fascicular architecture exhibiting clustered distribution of osteoclastic giant cells, surrounded by fibroblastic stromal cells along with reactive new bone formation. The differentials considered were CGCG (Central giant cell granuloma), GCT (Giant Cell tumor), ABC (Aneurysmal Bone Cyst) and Brown tumor. Serum Calcium and Serum PTH (Parathyroid hormone) were advised to ruleout brown tumor in histopathology report and for rest of the differentials excisional biopsy was suggested. Serum calcium and serum PTH were found to be raised. On further probing, the patient has been having right lower back pain and thin urine stream on and off for few months. USG abdomen was done for the same which revealed bilateral nephrolithiasis with left sided PUJ calculus causing gross hydronephrosis along with bilateral medullary nephrocalcinosis. DJ stenting was thus advised by the nephrologist. On identifying the primary cause, hemithyroidectomy with parathyroid removal was done. The decrease in parathyroid hormone level was drastic after the surgery. His urine stream was normal during his post –op stay at the hospital. The patient was advised for regular follow up.